Distributed and decentralized orchestration of containers on edge clouds - Pires, André (2021)
Cloud Computing has been successful in providing substantial amounts of resources to deploy scalable and highly available applications. However, there is a growing necessity of lower latency services and cheap bandwidth access to accommodate the expansion of IoT and other applications that reside at the internet's edge. The development of community networks and volunteer computing, together with the today's low cost of compute and storage devices, is making the internet's edge filled with a large amount of still underutilized resources. Due to this, new computing paradigms like Edge Computing and Fog Computing are emerging. This work presents Caravela a Docker's container orchestrator that utilizes volunteer edge resources from users to build an Edge Cloud where it is possible to deploy applications using standard Docker containers. Current cloud solutions are mostly tied to a centralized cluster environment deployment. Caravela employs a completely decentralized architecture, resource discovery and scheduling algorithms to cope with (1) the large amount of volunteer devices, volatile environment, (2) wide area networks that connects the devices and (3) nonexistent natural central administration.